Endogenous public information and welfare - Xavier Vives (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper performs a welfare analysis of economies with private information when public information is endogenously generated and agents can condition on noisy public statistics in the rational expectations tradition. We find that equilibrium is not (restricted) efficient even when feasible allocations share similar properties to the market context (e.g., linear in information). The reason is that the market in general does not internalize the informational externality when public statistics (e.g., prices) convey information. Under strategic substitutability, equilibrium prices will tend to convey too little information when the informational role of prices prevails over its index of 'scarcity' role and too much information in the opposite case. Under strategic complementarity, prices always convey too little information. These results extend to the internal efficiency benchmark (accounting only for the collective welfare of the active players). However, received results-on the relative weights placed by agents on private and public information, when the latter is exogenous- may be overturned.
Keywords: D82; D83; 330; information externality; strategic complementarity and substitutability; asymmetric information; team solution; rational expectations; schedule competition; behavioral traders